Linkage Program of Islamic Institutions and Government Institution for Empowering MSMEs: Evidence from Indonesia - Raditya Sukmana; Imron Mawardi; Tika Widiastuti; Taqiyah Dinda Insani; Nova Rini (Ekonomi Syariah IAIN Kudus, 2020)
The purpose of this study is to analyze how the linkage program of Islamic institutions and government institution in empowering MSMEs and analyze the increase in the range of empowerment. By using a qualitative research approach and descriptive analysis method, the results of this study indicate that there are four parties involved in the empowerment linkage program and each party has their respective roles in the aim of empowering MSMEs. Furthermore, there is also increasing in the range of empowerment in terms of the amount of empowerment program funding and improving the quality of MSME after participating in the empowerment program.